2018
DOI: 10.4314/jasem.v22i3.7
|View full text |Cite
|
Sign up to set email alerts
|

Micronucleus Assay and Heavy Metals Characterization of E-waste Dumpsites in Lagos and Osun States, Southwest Nigeria

Abstract: The contamination of the aquatic ecosystem with heavy metals arising from the discharge of electronic waste (e-waste) or seepage of leachate from open waste dumpsites is on the increase. The impact of e-waste leachate on the micronucleus (MN) of Tilapia guineensis and the levels of heavy metals (Pb, Cd, Cr, As, Hg, Al and Ba) in the sediments, water, leachate and aquatic fauna (Tilapia guineensis, Callinectes amnicola and Cardiosoma armatum) found in and around e-waste dumpsites in Lagos and Osun States was st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…Toxic and genotoxic levels can induce adverse ecological and human health effects. 16,39 Soil leachate and well water samples from the Alaba international and Computer village electronic markets in Lagos State, Nigeria showed both mutagenic and genotoxic properties in plant and animal models. 16,24,25,[40][41][42] Exposure of T. guineensis juveniles to varying concentrations of e-waste leachate could be genotoxic to fish.…”
Section: Health Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Toxic and genotoxic levels can induce adverse ecological and human health effects. 16,39 Soil leachate and well water samples from the Alaba international and Computer village electronic markets in Lagos State, Nigeria showed both mutagenic and genotoxic properties in plant and animal models. 16,24,25,[40][41][42] Exposure of T. guineensis juveniles to varying concentrations of e-waste leachate could be genotoxic to fish.…”
Section: Health Effectsmentioning
confidence: 99%
“…16,24,25,[40][41][42] Exposure of T. guineensis juveniles to varying concentrations of e-waste leachate could be genotoxic to fish. 39 Hazardous heavy metals such as As, Cd, Hg, Pb from e-waste are known to cause cancer. 43 In their study "Perceived public health effects of occupational and residential exposure to electronic wastes in Lagos, Nigeria" the authors reported cases of cancer among e-waste workers who had spent at least 6 years or more in e-waste sites.…”
Section: Health Effectsmentioning
confidence: 99%
“…Various researchers found that metal bioaccumulation in fish organs causes genotoxic consequences such as DNA damage, MN, Nas, etc. (Omar et al, 2012;Nagpure et al, 2015;Igbo et al, 2018). According to Hussain et al (2018), fish genotoxicity is a genotoxic indicator, and blood is a useful biomarker for assessing the risk of water pollution and genotoxin.…”
Section: Introductionmentioning
confidence: 99%